Frequency reliant wireless power transfer link for a applications of mWatts devices - Adam, Ismail; Khan, Sheroz; Zaharudin, Zarimin; Abdul Kader, Kushsairy; Abdul Rahman, Farah Diyana; Nordin, Anis Nurashikin; Che Musa, Nurul Arfah; Yaacob, Mashkuri (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
In general, the resonant inductive wireless power transfer is superior in power efficiency consequently provides longer transfer range over inductive or capacitive wireless power transfer. For that reason, the theoretical analysis and simulation results of the series-to-series wireless power transfer topology were discussed in this paper. The study is conducted to analyze the effect of the coupling coefficient (k) of the coupling coils to the resonant frequency and input impedance of the transmitting circuit. The analysis is conducted by analyzing the equivalent circuit model by using circuit theory. The equivalent circuit model is developed by using the T-equivalent circuit. Further, the result is validated with the circuit simulation using the ISIS Proteus simulation package. The results of the analysis used in developing the highly efficient series-to-series wireless power transfer.